Largest Investigation of Branching Patterns of the Popliteal Artery - Lin, Cen-Hung; Yeh, Jui-Po; Chen, Yun-Ting; Chen, Meng-Hsiang (Journal of Reconstructive Microsurgery, 2025)
Head and neck squamous cell carcinoma accounts for 4.5% of all new cancers diagnosed. A fibula free flap is often performed after tumor resection. Preoperative acknowledgment of the branching patterns of the popliteal artery is important to avoid flap failure or leg ischemia after flap harvest. We performed this extensive study using a modified classification to help thoroughly recognize variations.The subjects were Taiwanese patients who received radiologic examinations of their lower limbs at a single medical center from May 2006 to December 2022. Only digital subtraction angiography, computed tomography angiography, and magnetic resonance angiography, which reveal the vasculature of the lower limbs, were included. All images were viewed by the same plastic surgeon on the same computer screen. Statistical analysis was subsequently performed on the data.In total, 1,244 right legs and 1,198 left legs (2,442 legs in total) from 1,485 Taiwanese patients were included in this study. In addition to normal branching, type IA, other branching patterns as variations occurred in 4.1% (n = 100) of the included legs. The second and third common patterns were type IIIA (1.06%, n = 26) and IB (0.98%, n = 24), respectively. Forty-seven patients presented with variation and had both legs evaluated, and 29.8% of them presented with bilateral variations.A preoperative vascular examination is strongly recommended before harvesting a free fibular flap because some patients might have a blood supply to the foot and lower leg, mainly from the planned-to-be-harvested peroneal artery (PR), or might not have a workable PR. Using fibular vessels as a flap pedicle might not be able to be performed in up to 1.84% of legs.
Keywords: popliteal artery; branching; fibula flap